PENGARUH WORK LIFE BALANCE, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Thessha Adi Putri; Mardhiyah Dwi Ilhami (Yayasan Insani Mandiri Santani, 2026)
This study aims to analyze the effect of work-life balance, work discipline, and work motivation on employee performance at PT Sandabi Indah Lestari Ketahun Branch. The background of this research is based on the indication that employee performance has not been optimal, which is influenced by the balance between work and personal life, the level of discipline, and employees' work motivation.This research uses a quantitative approach with data collected through questionnaires. The analysis technique applied is multiple linear regression to determine the influence of each independent variable on the dependent variable.The results show that work-life balance, work discipline, and work motivation have a significant effect on employee performance, both partially and simultaneously. This indicates that better balance between work and personal life, higher discipline, and stronger work motivation can improve employee performance.Based on these findings, the company is expected to enhance employee performance by maintaining work-life balance, enforcing consistent discipline, and providing appropriate motivational support. Keywords: work-life balance, work discipline, work motivation, employee performance